The Role of Wishtleblowing as Mediation on the Effect of Organizational Justice on Employee Fraud - Parulian, Parulian; Bebasari, Nataliana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of organizational justice on employee fraud mediated by whistleblowing intention in the context of banking in Jakarta. The research sample consisted of 78 bank employees working in various branches in Jakarta. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through Smart PLS software. The results showed that organizational justice has a significant influence on employee cheating. This finding indicates that employees' perceptions of fairness in their workplace are directly correlated with the likelihood of fraud. In addition, the study also found that whistleblowing intentions serve as a mediator in this relationship, suggesting that the propensity to report unethical or suspicious activities is a key factor in reducing the incidence of fraud. These results have important implications for bank management in developing fraud prevention strategies, particularly through enhancing organizational justice and promoting a whistleblowing culture. This study provides new insights into the dynamics of employee fraud and its prevention mechanisms, highlighting the important role of organizational justice and whistleblowing intentions in the context of banking in Jakarta